The Role of Mediation of Work Motivation in Improving the Performance of BNN Employees in Central Kalimantan Province - Abd. Kadir (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine and analyze the effect of incentives and organizational culture on employee performance through the mediation role of work motivation at the National Narcotics Agency of Central Kalimantan Province. The method used in this research is quantitative research. The sample of this research is 70 people. The data were analyzed using the Structural Equation Modeling (SEM) model using the Partial Least Square approach (SEM-PLS). The results of the study showed that incentives have no significant effect on employee performance and work motivation. Meanwhile, organizational culture has a significant effect on employee performance and work motivation. In addition, work motivation has a significant effect on employee performance. For the mediating role of work motivation, the results showed that work motivation cannot mediate the relationship between incentives and employee performance (no mediation). Meanwhile, work motivation can mediate the relationship between organizational culture and employee performance partially (partial mediation).